La tradición manuscrita del Breviarium de Johannes de Sancto Paulo - Martín Ferreira, Ana Isabel; García González, Alejandro (Exemplaria Classica, 2010)
This article compiles the manuscript tradition of the Breviarium de signis, causis et curis morborum. This is an unpublished latin medical text, written by Johannes de Sancto Paulo in the twelfth century. This author is linked to the so-called Salerno Medical School. The testimonies of the codices provide data, hitherto unknown, about this author and his work.